Learning scenarios in safety at work in the scope of Polytechnic Higher Education courses - Ribeiro, J.E. (2022)
The Higher Professional Technical Courses (CTeSPs) of the Portuguese Polytechnic Higher Institutes correspond to a cycle of higher education studies that does not confer an academic degree. They have a duration of 2 years and the successful conclusion leads to obtaining a higher professional technician diploma. Given the specificity of this type of courses, the course units of their study plan must promote, whenever possible, more student-centred learning with a greater connection to practice. This approach has been followed in the Safety and Environment course unit classes of the CTeSPs in Chemical and Biological Analysis and Mechanical Technology and Vehicles of a Higher Education Institution in the North of Portugal, between the academic years 2016/2017 and 2020/2021. In this sense, and in the Safety component, tasks were proposed that, depending on the academic year in which they were performed, involved different scenarios: (1) laboratory context and (2) business context (study visits). In both cases, it was proposed to the students to carry out a practical work in group that intended to analyse the hazards and risks associated with aspects of the context in question, applying in a specific situation the contents of the course unit. This type of work was oriented so that there was knowledge sharing (lectures and group interaction) among students attending: (i) the course unit; (ii) the course unit in another CTeSP and (iii) another course unit in degree courses. In some situations, connections were established with other course units, within the same course, or in different courses. In this paper we intend to explain the different approaches applied, reflecting on their advantages/disadvantages and possible perspectives of adaptation to the other component of the course unit (Environment) or other courses.